Exploring the link between number of years since menopause and metabolic syndrome among women in rural China: a cross-sectional observational study. (3rd August 2018) - Zhou, Ying; Guo, Xiaofan; Sun, Guozhe; Yu, Shasha; Li, Zhao; Zheng, Liqiang; Sun, Yingxian
Abstract: The aim of this article was to explore the link between postmenopausal status according to years since menopause (YSM) and the prevalence of metabolic syndrome (MetS). This survey was conducted from January 2012 to August 2013. A total of 6022 women (3511, 58.3% were post-menopause) from Rural Northeast China were randomly selected and examined. The prevalence of the MetS was significantly higher in postmenopausal women (Post-MW) than in premenopausal women (Pre-MW) (55.0% vs. 33.1%, p .001). The risk for MetS in Post-MW increased with the number of YSM, reaching the peak level in the 5- to 9-year group (OR, 1.55; 95% CI, 1.23–1.96), and then decreased. The 5- to 9-year group had the highest risk of high glucose (OR, 1.48; 95% CI, 1.20–1.83) and high triglycerides (adjusted OR, 1.92; 95% CI, 1.53–2.41) whereas the risk for abdominal obesity, high BP, and low HDL-C was not significantly associated with the number of YSM. These findings suggested that, in China, Post-MW with 5–9 YSMs had the highest risk of MetS. YSM can be a useful screening tool to identify women at high risk for MetS.